2006
DOI: 10.4049/jimmunol.177.6.3515
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TLR9 and TLR2 Signaling Together Account for MyD88-Dependent Control of Parasitemia in Trypanosoma cruzi Infection

Abstract: Activation of innate immune cells by Trypanosoma cruzi-derived molecules such as GPI anchors and DNA induces proinflammatory cytokine production and host defense mechanisms. In this study, we demonstrate that DNA from T. cruzi stimulates cytokine production by APCs in a TLR9-dependent manner and synergizes with parasite-derived GPI anchor, a TLR2 agonist, in the induction of cytokines by macrophages. Compared with wild-type animals, T. cruzi-infected Tlr9−/− mice displayed elevated parasitemia and decreased su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
251
4
14

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(289 citation statements)
references
References 21 publications
20
251
4
14
Order By: Relevance
“…This suggests that TLR2 and TLR4 cooperate during T. gondii infection. Similar conclusions have been made in relation to cooperation between TLR2-TLR9 in mediating protection against Trypanosoma cruzi infection in mice (Bafica et al 2006), as well as in models of Mycobacterium tuberculosis infection (Bafica et al 2005). T. gondii heat shock protein 70 has also been implicated in maturation of dendritic cells via TLR4 (Aosai et al 2006) and an important indirect effect of TLR4 stimulation is seen in induction of inflammation in the small intestine following oral infection of mice due to substantial overgrowth of commensals in the ileum (Heimesaat et al 2007).…”
supporting
confidence: 61%
“…This suggests that TLR2 and TLR4 cooperate during T. gondii infection. Similar conclusions have been made in relation to cooperation between TLR2-TLR9 in mediating protection against Trypanosoma cruzi infection in mice (Bafica et al 2006), as well as in models of Mycobacterium tuberculosis infection (Bafica et al 2005). T. gondii heat shock protein 70 has also been implicated in maturation of dendritic cells via TLR4 (Aosai et al 2006) and an important indirect effect of TLR4 stimulation is seen in induction of inflammation in the small intestine following oral infection of mice due to substantial overgrowth of commensals in the ileum (Heimesaat et al 2007).…”
supporting
confidence: 61%
“…This latter phase is the period when most transmission to invertebrate hosts occurs. During the early stages of the acute phase, hosts survive because of strong innate immunity, mediated mostly by Toll-like receptors through the activation of the adaptor molecule MyD88 (Campos et al 2004, Bafica et al 2006, Bartholomeu et al 2008. However, to avoid elimination, the parasite manages to significantly delay the onset of the CD8 + T cell-mediated immunity (CMI) response (Martin et al 2006, Tzelepis et al 2006, 2007.…”
Section: Cd4 + and Cd8 + T Cells Are Important Factors In Mediating Hmentioning
confidence: 99%
“…A pivotal component of innate immunity is the intracellular protein MyD88, which represents the central adapter protein for the majority of the TLRs (1) identified to date (with the exception of TLR3) in addition to transducing activation signals emanating from the IL-1 and IL-18 receptors (14 -16). Previous studies have demonstrated that MyD88 knockout (KO) 3 mice exhibit dramatic defects in antibacterial immunity in a variety of infectious disease models, highlighting the importance of this adapter in influencing a wide array of host responses (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%